1991
DOI: 10.1111/j.1432-1033.1991.tb15805.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, cytotoxic and pharmacokinetic properties of an immunotoxin composed of a mouse monoclonal antibody Fib75 and the ribosome‐inactivating protein α‐sarcin from Aspergillus giganteus

Abstract: An immunotoxin was synthesized by the attachment of a-sarcin, the ribosome-inactivating protein derived from the mould Aspergillus giganteus, to a monoclonal mouse IgG2a antibody Fib75. The a-sarcin immunotoxin exerted toxic effects in tissue culture against the EJ human bladder carcinoma cell line, expressing the antigen recognised by the Fib75 antibody, inhibiting the incorporation of [3H]leucine by 50% at a concentration of 0.46 nM. The cytotoxic effects of the a-sarcin immunotoxin were indistinguishable fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…5A). Extensive degradation of 28 S RNA in ribosomes by Lys 13 -Leu 23 deletion mutants suggests that this region in the fungal ribotoxin is involved in modulating the activity and specific recognition of the cleavage site in the ribosome. Results obtained from assays using synthetic ␣-sarcin loop (a 35-mer) as substrate showed that deletions in regions Lys 13 …”
Section: Mutant Construction and Proteinmentioning
confidence: 99%
“…5A). Extensive degradation of 28 S RNA in ribosomes by Lys 13 -Leu 23 deletion mutants suggests that this region in the fungal ribotoxin is involved in modulating the activity and specific recognition of the cleavage site in the ribosome. Results obtained from assays using synthetic ␣-sarcin loop (a 35-mer) as substrate showed that deletions in regions Lys 13 …”
Section: Mutant Construction and Proteinmentioning
confidence: 99%
“…In fact, different ribotoxins have been used as components of immunotoxins [117][118][119][120][121][122][123][124][125]. The first ribotoxin-based immunotoxins were constructed by chemical conjugation with mitogillin [122], restrictocin [117][118][119], or α-sarcin [121]. Some years later second-generation versions were also produced by fusing restrictocin cDNA with that encoding the scFv region of a monoclonal antibody directed against the human transferrin receptor, joined by a linear flexible peptide to promote the independent folding of the two immunotoxin moieties.…”
Section: Ribotoxins As Part Of Immunotoxinsmentioning
confidence: 99%
“…However, although not so frequently employed, ribotoxins have several advantages for their use in the design of immunotoxins; namely, their small size, high thermostability, poor immunogenicity, resistance to proteases, and their highly efficient ability to inactivate ribosomes [3,4,117]. In fact, different ribotoxins have been used as components of immunotoxins [117][118][119][120][121][122][123][124][125]. The first ribotoxin-based immunotoxins were constructed by chemical conjugation with mitogillin [122], restrictocin [117][118][119], or α-sarcin [121].…”
Section: Ribotoxins As Part Of Immunotoxinsmentioning
confidence: 99%
“…Tumour localisation is significantly enhanced for ricin A chain immunotoxins made with antibody Fab' or F(ab')2 fragments compared with analogous immunotoxins made with intact antibody (Fulton et al, 1988a;Rostaing-Capaillon & Casellas, 1990). The molecular size of immunotoxins can also be reduced by selecting smaller toxin components such as asarcin or restrictocin which form immunotoxins having comparable potency to those made with the larger plant-derived toxin A chains or RIPs (Orlandi et al, 1988;Conde et al, 1989;Wawrzynczak et al, 1991c (Stoudemire et al, 1990). In further clinical trials of the anti-melanoma immunotoxin, attempts have been made to increase the duration of therapy by suppressing the host response with cyclophosphamide, prednisone, azathioprine and cyclosporin A, used singly or in combination (Spitler et al, 1989;Oratz et al, 1990).…”
Section: Toxin Structure and Actionmentioning
confidence: 99%